Pengembangan Seni Lukis Kaca di Desa Nagasepaha Kabupaten Buleleng dalam Mendukung Industri Kreatif - I Wayan Setem (Institut Seni Indonesia Surakarta, 2022)
Glass painting is a unique traditional art in Nagasepaha Village, Buleleng, Bali which has been designated as an Intangible Cultural Heritage by UNESCO in 2020. Glass painting in Nagasepaha Village has relatively long historical roots. Pioneered by Jro Dalang Diah in 1927, it continues to be passed down from generation to generation. Glass painting became one of the main sources of people’s livelihoods in Nagasepaha until now. The product of wayang glass painting is in great demand by both domestic and overseas art collectors due to its unique decorative and naturalistic style. However, currently glass painting faces many challenges to simply survive, especially when faced with various problems that resulted from the Covid-19 pandemic when many glass painters then switched professions. The social restrictions imposed by the government also impact the market and the weakening of people’s purchasing power. For this reason, a breakthrough with the right efforts is strongly necessary for glass painting to survive as a traditional art of Nagasepaha Village which has been proven in the past to be able to improve its people economy. The strategy that is considered appropriate for its development is by synergizing two revitalization concepts, namely the concept of diversifying painting techniques accompanied with textual and contextual revitalization. The revitalization of painting process and techniques is to strengthen indigenous skills to be able to apply them to more diverse media. Textual and contextual revitalization is carried out by applying new products that are varied and more adaptive to today’s market tastes.